Dominus Litis Restorative Model: Reconstruction of the Role of the Prosecutor in Criminal Procedure Law Against Perpetrators with Mental and/or Intellectual Disabilities - Dera, Alfa; Hasibuan, Fauzie Yusuf; Kristiawanto , Kristiawanto (Sahabat Publikasi, 2025)
This study aims to examine and formulate a restorative justice-based concept to strengthen the role of prosecutors as dominus litis in criminal procedure law concerning offenders with mental and/or intellectual disabilities (PMID). Despite Indonesia’s ratification of the Convention on the Rights of Persons with Disabilities (CRPD), the current criminal procedure system remains formalistic and fails to provide equitable legal protection for vulnerable groups. Using a normative juridical method combined with doctrinal and comparative approaches, this study analyzes relevant laws, practices, and empirical data. Findings reveal that prosecutors currently act merely as procedural agents for court referral, with no legal discretion to divert or dismiss cases restoratively. The absence of judicial-health assessments and lack of interdisciplinary collaboration result in discriminatory prosecution of mentally disabled offenders. This research proposes a restorative dominus litis model, integrating prosecutorial discretion, forensic mental health assessments, and legal mechanisms for restorative case resolution. The model supports the reform of Indonesia’s criminal procedure law toward a more inclusive, humane, and rights-based justice system.